Q. 244.8( 4 Votes )

Prove that: <span

Answer :

Formula: - (i) sin2x = 2sinxcosx


(ii)


L.H.S = Sin3x + sin2x – sinx = sin3x – sinx + sin2x


Applying formula (ii) we get,






= R.H.S


Hence, Proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics